Contribuição da experiência percepto-motora para o desempenho de habilidades manuais em lactentes, crianças e jovens com incapacidades - Campos, Ana Carolina de (2012)
Voluntary manual actions over objects emerge during the first half year of infants lives. These actions evolve from an exploratory characteristic to functional manipulative use of objects and its development is mediated by the limbs motor skill, by the experience in the task, and by the object properties. Research in the field has suggested that the perceptual-motor experiences arising from manual actions change the infants interactions with the world and impact their motor, perceptual and cognitive development. The first study of this manuscript is a literature review aimed at gathering information on the role of risk factors for developmental delay in the performance of exploratory actions over objects, and on the theoretical and methodological aspects underlying the assessment of these actions. The results from Study 1 showed that different risk conditions affect infants performance in particular ways. Few studies have investigated the early development of exploratory actions in infants at risk and taken into account the remarkable changes in motor skill seen in the period of emergence of reaching. Therefore, in Study 2 the development of exploratory actions was assessed in 16 typically-developing (TD) infants and 9 infants with Down syndrome (DS) at the age of reaching onset and the two subsequent months, considering the infants group and the object properties of size and rigidity. The results showed that infants with DS reach for and explore objects less frequently than TD infants, especially the small objects. Infants from both groups changed the amount of reaches with the experience in grasping, but only TD infants changed the amount of exploration in the same period. Pre-grasping actions were different for each object, but less efficient in generating action-relevant information in the DS group. These infants also performed fewer behaviors that required greater motor skill. To obtain a longitudinal view of the development of manual actions, 13 of the same participants were reassessed at the age 2 years, and the results are presented in Study 3. This study showed that children with DS at that age have difficulties in manipulating objects, especially in performing anticipatory adjustments to small objects and sequential strategies required to manipulate objects with complex shapes. The child s group was predictive of the fine motor and cognitive performance assessed by the Bayley Scales of Infants and Toddler Development Third edition, in that children with DS had inferior performance compared to the TD group. The ability to grasp objects in the period after reaching onset was predictive of the performance in the fitting task in both groups. This result shows the contribution of perceptual-motor experience in early developmental stages to the performance of manual actions later in life. Finally, in Study 4 it was assessed the hand function in 11 individuals with hemidystonia and 9 healthy volunteers. Bilateral sensory and motor deficits were found in the hemidystonia group, and these deficits were correlated with the hand impairment level. Taken together, the results show that manual skills emerge and are modified by the individuals perceptual-motor experiences and that reduced experiences may impact the functional performance of people with disabilities throughout the development.